Mothers, Domestic Violence, and Child Protection: The UK Response - Stewart, Stacey (Violence against women, 2023)
Research highlights that mothers are often blamed for their child's exposure to domestic abuse and they are given a leave ultimatum. This article furthers discussion, guided by the question “how do (UK) mothers with violent partners experience social work interventions?” Nineteen mothers located around England and Wales were interviewed. Data were analyzed using deductive thematic analysis. The findings resonate with research from a decade earlier showing mothers felt blamed and were responsibilized for the violence they experienced and given the leave ultimatum by social workers. This article calls for a change in social work practice for mothers experiencing domestic abuse.